Hybrid Genotype of Anisakis simplex (s.s.) and A. pegreffii Identified in Third- and Fourth-Stage Larvae from Sympatric and Allopatric Spanish Marine Waters - Xavier Roca-Geronès; M. Magdalena Alcover; Carla Godínez-González; Isabel Montoliu; Roser Fisa (Animals, 2021)
The sibling species Anisakis simplex (s.s.) and Anisakis pegreffii are parasites of marine mammals and fish worldwide and the main causative agents of human anisakiasis. In sympatric areas, a hybrid genotype between the two species has been identified, mainly in third-stage larvae, but rarely in fourth-stage and adult forms. The aim of this study was to confirm the presence of hybrid genotypes in larvae parasitizing fish caught in sympatric and allopatric Spanish marine waters, the North-East Atlantic and West Mediterranean, respectively, and to study possible differences in the growth behaviour between genotypes. Of the 254 molecularly analysed larvae, 18 were identified as hybrids by PCR-RFLP analysis of the rDNA ITS region, 11 of which were subsequently confirmed by EF1 α-1 nDNA gene sequencing. These results therefore indicate an overestimation of hybrid genotypes when identification is based only on the ITS region. We also report the detection of a hybrid specimen in a host from the West Mediterranean, considered an allopatric zone. Additionally, fourth-stage larvae with a hybrid genotype were obtained in vitro for the first time, and no differences were observed in their growth behaviour compared to larvae with A. simplex (s.s.) and A. pegreffii genotypes.